Microwave-Assisted Extraction of Phlorotannins from Fucus vesiculosus - Sónia J. Amarante; Marcelo D. Catarino; Catarina Marçal; Artur M. S. Silva; Rita Ferreira; Susana M. Cardoso (Marine Drugs, 2020)
Microwave-assisted extraction (MAE) was carried out to maximize the extraction of phlorotannins from Fucus vesiculosus using a hydroethanolic mixture as a solvent, as an alternative to the conventional method with a hydroacetonic mixture. Optimal MAE conditions were set as ethanol concentration of 57% (v/v), temperature of 75 °C, and time of 5 min, which allowed a similar recovery of phlorotannins from the macroalgae compared to the conventional extraction. While the phlorotannins richness of the conventional extract was slightly superior to that of MAE (11.1 ± 1.3 vs. 9.8 ± 1.8 mg PGE/g DWextract), both extracts presented identical phlorotannins constituents, which included, among others, tetrafucol, pentafucol, hexafucol, and heptafucol structures. In addition, MAE showed a moderate capacity to scavenge ABTS•+ (IC50 of 96.0 ± 3.4 µg/mL) and to inhibit the activity of xanthine oxidase (IC50 of 23.1 ± 3.4 µg/mL) and a superior ability to control the activity of the key metabolic enzyme α-glucosidase compared to the pharmaceutical drug acarbose.